Fragmentation of packets in the radio data channels (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2016)
Introduction. Effective data transmission speed in the radio data channels network is determined by the parameters of the exchange report on the data link layer and physical levels and the wave emission channel characteristics. For guaranteed delivery of packets the technology with the supervision of packages receiving validity by consumer is used. Errors availabilities in packets demand retransmission, which leads to a decrease the effective data transmission speed. Fragmentation of packets reduces the probability of an error in the packet, the delay of the fragment retransmission, which improves the effective transmission speed. Problem statement. The maximum packet length for data link layer and physical levels is determined according to the conditions of the effective network functioning in general, consequently the packet length with low values of bit error in the channel can be significantly less than optimal, and with large values of bit error the possibility to select the division fragments of the maximum length into equal parts exists, under the terms of improving effective transmission speed. The aim of this work is to build analytical model for points determination on the scale of probability of bit errors, where the length of packet fragments is necessary to be changed in order to better efficiency of data transmission speed. Theoretical results. Based on the analysis of data transmission report with a stoppage and expectations the analytical model of effective data transmission speed in the radio data channel with bit errors and random distribution is received. There is equation to calculate the bit errors probability at the points of the fragments length changing. The obtained analytical solutions of the equations allow calculating the value of the bit errors probability for any parameters of data transmission cycle. Also, analytical expressions for calculating the optimal fragments length with a given probability of bit errors and probability of bit errors for a given fragment length are obtained. Conclusion. Proposed analytical model and analytical calculations can be used on data link layer and physical levels of the channels with packet data transmission according to the ARQ SAW algorithm to select parameters of fragmentation depending on the bit errors in the channel.